2018
DOI: 10.5713/ajas.17.0679
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone beta gene polymorphism and its effect on semen quality traits and luteinizing hormone concentrations in Murrah buffalo bulls

Abstract: ObjectivePresent investigation was aimed to study the Single Nucleotide Variants of the luteinizing hormone beta (LHβ) gene and to analyze their association with the semen quality (fresh and post-thawed frozen semen) and luteinizing hormone (LH) concentrations in Murrah buffalo bulls.MethodsPolymerase chain reaction–single stranded conformational polymorphism (PCR–SSCP) and Sanger sequencing method is used to study genetic variability in LHβ gene. LH assay was carried out using enzyme-linked immunosorbent assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The primary regulator of mammalian reproductive function in both males and female is GnRH Biological Signalling Pathway and it acts via G-protein coupled receptors to stimulate synthesis and secretion of two gonadotropin hormones like luteinizing hormone and follicle-stimulating hormone (41) . Luteinizing hormone beta polypeptide ( LHβ ) gene is a single copy gene and it has been indicated that a mutation in the coding region of the gene could lead to its in activation and consequent impaired production of leydig cells (42) and leading to infertility in human. It also observed that the mutation would lead to susceptibly to prostate cancer via altered testosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The primary regulator of mammalian reproductive function in both males and female is GnRH Biological Signalling Pathway and it acts via G-protein coupled receptors to stimulate synthesis and secretion of two gonadotropin hormones like luteinizing hormone and follicle-stimulating hormone (41) . Luteinizing hormone beta polypeptide ( LHβ ) gene is a single copy gene and it has been indicated that a mutation in the coding region of the gene could lead to its in activation and consequent impaired production of leydig cells (42) and leading to infertility in human. It also observed that the mutation would lead to susceptibly to prostate cancer via altered testosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Alters the function of the HESX1 protein and represses the activity of other genes, disrupting the formation and early development of the The SNP named G1052A has been reported [44]. Six other SNPs were also identified and are gC356090A, gC356113T, gA356701G, gG355869A, gG356330C, and gG356606T [45].…”
Section: Fmr1 (Fragile X Mental Retardation 1)mentioning
confidence: 99%